Impak Pandemi Covid-19 dan Pembangunan Jalan Tol terhadap Pendapatan UMKM - Nadila Utari; Vidya Fathimah (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of the Covid-19 pandemic and toll road construction on the income of Dodol MSMEs in the Workshop Market, Perbaungan District. This research method is quantitative. Primary and secondary data and research methods using hypothesis testing, normality testing, multiple linear regression testing, and simultaneous testing, all of which are used in data analysis techniques. The results showed that with an alpha level of 0.05 and a significance level of F-count <F-table of 0.008, the simultaneous test results revealed that Fcount = 321.572 > Ftable = 3.41. Therefore, the covid 19 variable and the construction of the toll road simultaneously have a good and big impact on the income of the Dodol UMKM in the Workshop Market, Perbaungan District. The Covid-19 variable partially has a negative and significant effect on income as indicated by the results of the partial T-test finding that the Covid-19 Pandemic variable has a value of -15.156 T-table 1.771 and a significant level of 0.004 lower than alpha (0.05). For the road construction variable, toll road construction has a T-count of -31.318 < T-table 1.771 and a significance value of 0.010 is smaller than alpha (0.05), so partially the toll road construction variable has a negative and significant effect on income. In conclusion, the income of Dodol UMKM at the Workshop Market in Perbaungan District was negatively and significantly affected due to the Covid 19 pandemic and the construction of the toll road, which fell by 40%. Keywords: Covid-19 Pandemic, Toll Road Construction, MSME Income